2016
DOI: 10.1038/ncomms11668
|View full text |Cite
|
Sign up to set email alerts
|

Geometric spin echo under zero field

Abstract: Spin echo is a fundamental tool for quantum registers and biomedical imaging. It is believed that a strong magnetic field is needed for the spin echo to provide long memory and high resolution, since a degenerate spin cannot be controlled or addressed under a zero magnetic field. While a degenerate spin is never subject to dynamic control, it is still subject to geometric control. Here we show the spin echo of a degenerate spin subsystem, which is geometrically controlled via a mediating state split by the cry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Moreover, B ac from these sources is linearly polarized, while the NV spin has clear transition selection rules; The m S = 0 ↔ 1 (−1) transition is driven by σ + (σ − ) circularly polarized fields. To fully exploit the S = 1 nature of the NV spin for quantum information and metrology applications, [11][12][13][14] it is highly desired to have a reliable means to generate arbitrarily polarized microwave fields.…”
Section: -7mentioning
confidence: 99%
“…Moreover, B ac from these sources is linearly polarized, while the NV spin has clear transition selection rules; The m S = 0 ↔ 1 (−1) transition is driven by σ + (σ − ) circularly polarized fields. To fully exploit the S = 1 nature of the NV spin for quantum information and metrology applications, [11][12][13][14] it is highly desired to have a reliable means to generate arbitrarily polarized microwave fields.…”
Section: -7mentioning
confidence: 99%
“…The previously demonstrated robustness against electric field noise and temperature drift [32], and enhancement of magnetic field sensitivity [33] in double quantum qubit utilizing ms=±1 states in a three-level system can also be adapted to our qubit. Moreover, it has been demonstrated that the degeneracy of our qubit is required for interfacing with photon polarization [23,24], and that the coherence time in a low magnetic field regime is maximized under a zero magnetic field [9,31].…”
mentioning
confidence: 99%
“…As alternatives, a composite pulse technique for achieving high-fidelity gates [3,4] and a specially designed gate sequence [2,5,6] have been developed to be independent of the initial state.A qubit is typically defined as being in a two-level system with an energy gap, which allows direct transition within the bases to implement dynamic quantum gates. Another type of qubit can also be defined in a two-level system without an energy gap; this type requires an indirect transition via a third ancillary level, and thus constitutes a V-shaped three-level system to implement geometric quantum gates [9][10][11][12]. Geometric quantum gates can be either adiabatic [13][14][15] or non-adiabatic [9][10][11][12][16][17][18][19].…”
mentioning
confidence: 99%
See 2 more Smart Citations